Transcriptome and Proteome Analysis in LUHMES Cells Overexpressing Alpha-Synuclein - Höllerhage, Matthias; Stepath, Markus; Kohl, Michael; Pfeiffer, Kathy; Chua, Oscar Wing ho; Duan, Linghan; Hopfner, Franziska; Eisenacher, Martin; Marcus, Katrin; Höglinger, Günter U. (Frontiers in Neurology, 2022)
LUHMES cells share many characteristics with human dopaminergic neurons in the substantia nigra, the cells whose demise is responsible for the motor symptoms in Parkinson’s disease (PD). LUHMES cells can therefore be used bona fide as a model to study pathophysiological processes involved in PD. Previously, we showed that LUHMES cell degenerate after six days upon overexpression of wild type alpha-synuclein. In the present study we performed a transcriptome and proteome expression analysis in alpha-synuclein-overexpressing cells and GFP-expressing control cells in order to identify genes and proteins that are differentially regulated upon overexpression of alpha-synuclein. The analysis was performed four days after the initiation of alpha-synuclein or GFP overexpression, before the cells died, in order to identify processes that preceded cell death. After adjustments for multiple testing, we found 765 genes being differentially regulated (439 upregulated, 326 downregulated) and 122 proteins being differentially expressed (75 upregulated, 47 downregulated). In total, 21 genes and corresponding proteins were significantly differentially regulated in the same direction in both datasets, of these 13 up- and 8 downregulated. In total, 13 genes and 9 proteins were differentially regulated in our cell model, which had been previously associated with PD in recent genome-wide association studies (GWAS). In the gene ontology (GO) analysis of all upregulated genes, the top terms were “regulation of cell death”, “positive regulation of programmed cell death”, and “regulation of apoptotic signaling pathway”, showing a regulation of cell death-associated genes and proteins already two days before they started to die. In the GO analysis of the regulated proteins, amongst the strongest enriched GO terms were “vesicle”, “synapse”, and “lysosome”. In total, 33 differentially regulated proteins were associated with synapses and 12 differentially regulated proteins were associated with the “lysosome”, suggesting that these intracellular mechanisms, which had been previously associated with Parkinson’s disease, also play an important role in our cell model.